APLICACIÓN DE LAS TECNOLOGÍAS DE LA INFORMACIÓN Y LA COMUNICACIÓN A LA MEJORA DE LA PARTICIPACIÓN EN LOS CUERPOS COLEGIADOS - Matilde Rissi (Universidade Federal de Santa Catarina, 2016)
It is frecuent, at least in the Argentine Republic, to listen in the Institutions of Higher Education that the participation of the members of the University Community in the Governing Bodies, is carried out with little informat ion or with limited access to the antecedents in question. This happens fundamentally in those spaces that analyze and dictate with respect to the procedures treated in The Collegiate Bodies. This situation is aggravated in the case of institutions that ar e geographically deconcentrated which ends up relegating, or directly excluding, the participation of those who carry out activities in the most distant locations of the place where the Collegiate Bodies operate. This situation occurs in the National Unive rsity of Luján (UNLu), Argentina, since its teaching, research and extension activities are carried out in six Headquarters, Central Headquarters, three Regional Centers and two Academic Delegations. Based on this need, we developed a project that aims to use a Content Manager, who has free access, to communicate the issues that come to treatment and also the background of the people who participate in the Advisory Committees of the Honorable Superior Council. It is expected with this proposal to improve th e participation of those who are not at Central Headquarters.